2007
DOI: 10.1097/01.brs.0000261561.12944.ff
|View full text |Cite
|
Sign up to set email alerts
|

Modic Changes in Endplates of Lumbar Vertebral Bodies

Abstract: Modic changes at L5-S1 and Modic type I lesions are more likely to be associated with pain symptoms than other types of Modic changes or changes located at other lumbar levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
112
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(125 citation statements)
references
References 26 publications
12
112
0
1
Order By: Relevance
“…In accordance with earlier observations that MCs are rare in children [12] and young adults [26], but common in middle-aged adults [9], the current study confirmed an association between age and the presence of MCs. Moreover, older age was associated with a greater number of endplates affected and MCs of larger size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with earlier observations that MCs are rare in children [12] and young adults [26], but common in middle-aged adults [9], the current study confirmed an association between age and the presence of MCs. Moreover, older age was associated with a greater number of endplates affected and MCs of larger size.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence rate was relatively high, but is consistent with results of previous studies of MCs in 55% of Finnish male train engineers (age range 36–56 years) [9] and 49% of 44-year-old Danes [8]. According to systematic reviews MCs are more prevalent in back pain patients than in asymptomatic volunteers, in adults than in adolescents and younger children, and more common in Europeans than in Asians [23,24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…MCs are notably common in people who have the relevant symptoms1. The importance of MCs has been highlighted in many studies due to their association with low back pain (LBP)23. Three different types of subchondral signal abnormalities in the vertebral body marrow were first independently described by de Roos et al 4.…”
mentioning
confidence: 99%
“…A number of studies have emphasized the importance of understanding the microstructure of the endplate, especially the canal network in the endplate111217313233343536. It has been reported that nutrients are supplied to the IVD mainly via diffusion through the canals in the endplate1137.…”
Section: Discussionmentioning
confidence: 99%